2004
DOI: 10.1111/j.1365-2486.2004.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest and agricultural land‐use‐dependent CO2 exchange in Thuringia, Germany

Abstract: Eddy covariance was used to measure the net CO 2 exchange (NEE) over ecosystems differing in land use (forest and agriculture) in Thuringia, Germany. Measurements were carried out at a managed, even-aged European beech stand (Fagus sylvatica, 70-150 years old), an unmanaged, uneven-aged mixed beech stand in a late stage of development (F. sylvatica, Fraxinus excelsior, Acer pseudoplantanus, and other hardwood trees, 0-250 years old), a managed young Norway spruce stand (Picea abies, 50 years old), and an agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 30 publications
(48 reference statements)
6
88
3
1
Order By: Relevance
“…Similar behaviour has been observed elsewhere, for forests as well as agricultural sites. For example, Anthoni et al (2004) reported that the uncertainties in annual NEE for ±0.1 m s −1 variation of the u * threshold ranged from 9 to 62 g C m −2 yr −1 across four sites in different ecosystems. The threshold-dependent variations of NEP at the IFR and UUW sites are of same sign and comparable magnitude as those of Anthoni et al (2004).…”
Section: Carbon Budget Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behaviour has been observed elsewhere, for forests as well as agricultural sites. For example, Anthoni et al (2004) reported that the uncertainties in annual NEE for ±0.1 m s −1 variation of the u * threshold ranged from 9 to 62 g C m −2 yr −1 across four sites in different ecosystems. The threshold-dependent variations of NEP at the IFR and UUW sites are of same sign and comparable magnitude as those of Anthoni et al (2004).…”
Section: Carbon Budget Uncertaintymentioning
confidence: 99%
“…For example, Anthoni et al (2004) reported that the uncertainties in annual NEE for ±0.1 m s −1 variation of the u * threshold ranged from 9 to 62 g C m −2 yr −1 across four sites in different ecosystems. The threshold-dependent variations of NEP at the IFR and UUW sites are of same sign and comparable magnitude as those of Anthoni et al (2004). Both GPP and ER increased with increasing data-gap fraction but the latter variable showed the stronger dependence in line with NEP decreasing with increasing data-gap fraction.…”
Section: Carbon Budget Uncertaintymentioning
confidence: 99%
“…), which was amply used for eddy covariance measurements (e.g. Anthoni et al, 2004) or biomass modelling (Wirth et al, 2004). The site is characterized by mono-specific Norway spruce (Picea abies L.) stands.…”
Section: Site Sampling and Datamentioning
confidence: 99%
“…These studies typically compare microclimate and fluxes of GHGs from pastures and/or crops with adjacent for-est ecosystems under a range of management conditions (e.g. Anthoni et al, 2004;Zona et al, 2013) or natural grasslands and different cropping types (e.g. Zenone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%